The Correlation between RDW, PDW, and NLR with the SOFA Score in Septic Patients - Linda Mayliana Kusumaningrum Nurtadjudin; Irda Handayani; Agus Alim Abdullah; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Sepsis is one of the main causes of mortality in the intensive care unit. The SOFA score is used to assess organ dysfunction. There are several markers of sepsis such as the combination of RDW, PDW, and NLR to help predict the outcome of sepsis. To determine the role of RDW, PDW, and NLR associated with SOFA scores as prognostic markers in sepsis. A retrospective study with a cross-sectional approach has been conducted using secondary data from the medical records of sepsis patients from January 2018 to December 31, 2020, who met the inclusion criteria and were admitted to the ICU of Dr. Wahidin Sudirohusodo Hospital, Makassar. The sample size was 109 people consisting of 62 (56.9%) males and 47 (43.1%) females. The highest age range is 56–65 years (37.6%). A total of 97 people (89%) died and 12 (11%) improved. There is a positive correlation between changes in RDW and changes in SOFA scores (p=0.031), there is a positive correlation between changes in PDW and changes in SOFA scores (p=0.000), and there is a positive correlation between changes in NLR and changes in SOFA scores (p=0.000). The increase of RDW caused by systemic inflammation can predict disease progression. The state of increased proinflammatory cytokines inhibits the proliferation and maturation of erythrocytes; hence, it causes an increase in RDW. The acceleration of platelet destruction due to the suppression of cytokines in the bone marrow increases PDW. The increase in NLR occurs due to the rise in the inflammatory response, which results in suppressed cellular immunity. RDW, PDW, and NLR are positively correlated with changes in SOFA scores. PDW and NLR have a significant correlation with the outcome. RDW, PDW, and NLR can be used as prognostic markers in septic patients